Bending The Golden Giant: Indonesia's Bargaining Power for Nationalized Control Over PT. Freeport Indonesia - Abdurofiq, Atep; Kusumawardhana, Indra (Universitas Sultan Ageng Tirtayasa, 2024)
From 2009-2017, the renegotiation process between Indonesia and PT Freeport Indonesia (PTFI) has provided crucial insights into the International Political Economy's (IPE) understanding of the relationship between developing nations and Multi-National Corporations (MNCs). This paper delves deep into the evolving dynamics between Indonesia and Freeport McMoRan, spotlighting the concept of state capacity as a lens to decipher the nuances of bargaining power in the realm of natural resource extraction. Advocating an original perspective, our study charts a strategic path for developing nations to reassert control over their natural resources vis-à-vis MNCs. At its core, this research underscores the enduring sovereignty of states, albeit adapted to the demands of an increasingly globalized world. The outcomes bolster the argument that, even in a globalized context, states retain the capability to harness their sovereign standing, enabling them to negotiate effectively with MNCs.